Tafsir Religiositas Cinta terhadap Buku Puisi Ijinkan Aku Mencintaimu Karya Abdul Wachid B.S. - Riana Anjarsari Riana Anjarsari (CV. Multi Kreasi Media, 2022)
The discussion of the religiosity of love leads to the appreciation of love which is based on religious values ​​in an exoteric depth dimension. The thought of the religiosity of love questions an appreciation of love so that love relationships are colored with sincerity. In the book of poetry